PERITONEAL DIALYSIS AND PERITONITIS : A SYSTEMATIC REVIEW - Effendy, Kgs. Mahendra (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
The chronic kidney disease (CKD) epidemic is a problem that affects people all over the world. The incidence and frequency of renal failure have both been on the increase, and this trend has been seen in a variety of different countries. Renal failure is correlated with unfavorable outcomes and high costs. Patients who have chronic kidney disease should have an early diagnosis and treatment of the underlying cause, as well as secondary preventative measures, if possible. This action may halt, or at the very least, significantly slow down the course of the illness. Patients who need urgent medical care for their CKD should spend their attention on the following: delaying or halting the course of CKD, detecting and treating pathological symptoms of CKD, and timely planning for long-term renal replacement therapy. Peritoneal dialysis, sometimes referred to as PD, is a treatment for kidney failure in which the lining of the abdomen, commonly referred to as the belly, is used in order to filter blood internally inside the body. This treatment is frequently referred to as "belly dialysis." Infection of the peritoneum is a common and potentially life-threatening complication of peritoneal dialysis (PD). Despite the fact that there were a significant number of individuals suffering from peritonitis, the rates of recurrence, relapse, and repetition were very low. The vast majority of individuals who had peritonitis for the first time were able to achieve a full recovery from the illness. Gram-positive peritonitis was most often caused by S. epidermidis, E. faecalis, and E. coli, whereas gram-negative peritonitis was most frequently caused by E. coli. Gram-positive bacteria are the main cause of PD-associated peritonitis. Although the incidence of PD-associated peritonitis is high, they have a high cure rate.